Ein Grosses Jahrzehnt Amerikanischer Kunst : Sammlung Prof. Dr. Peter Ludwig Köln-Aachen. - Alloway, Lawrence; Ammann, Jean-Christophe; André, Carl; Becker, Wolfgang; Chase, Linda; Dienst, Rolf-Gunter; Estes, Richard; Glaser, B.; Hanson, Duane; Honnef, Klaus; Imdahl, Max; Kanovitz, Howard; et al. (Luzern : Kunstmuseum Luzern, 1973)
Andre, Carl ; de Andrea, John ; Artschwager, Richard ; Bechtle, Robert ; Close, Chuck ; Dine, Jim ; Eddy, Don ; Estes, Richard ; Goings, Ralph ; Hanson, Duane ; Indiana, Robert ; Johns, Jasper ; Kanovitz, Howard ; Kelly, Ellsworth ; Lichtenstein, Roy ; Louis, Morris ; McLean, Richard ; Morley, Malcolm ; Morris, Robert ; Oldenburg, Claes ; Rauschenberg, Robert ; Rosenquist, James ; Salt, John ; Sarkisian, Paul ; Smith, Leon Polk ; Stella, Frank ; Twombly, Cy ; Warhol, Andy
biografie, bibliografie
Ein Grosses Jahrzehnt Amerikanischer Kunst : Sammlung Prof. Dr. Peter Ludwig Köln-Aachen, Kunstmuseum Luzern, 15. Juli - 16. September 1973
Duits
boek
Keywords: Amerika